THE EDUCATION RELATIONSHIP DEVELOPMENT BETWEEN CHINA AND INDONESIA AS ASEAN MEMBER - Adi Maulana (EduLite: Journal of English Education, Literature and Culture, 2018)
China and ASEAN have long history on their relationship. One of ASEAN countries, Indonesia, along with China are two big countries in Asia with similar national interests and objectives in partnership, which are peace and prosperity of G20, APEC, 10+1, and 10+3, in which Indonesia is an active participant. One of the cooperation between China and ASEAN is through education. Indonesia may promote student exchange as well as proposing the idea of students exchange in various forums such as ASEAN-China free-trade, culture, tourism, education and many others. However, the data shown that the proportion of ASEAN students in China do not reflect the proportion of population of each ASEAN countries.  Indonesia, the largest country by population, only sends the second biggest number of students to China behind Thailand, which puts the most students in China Education.  This paper discusses the ups and downs of Indonesia-China relationship in education. SWOT analysis is used to see Indonesia-China relationship in the perspective of ASEAN. It can be concluded that cooperation among countries is inevitable measure facing the more challenging world. However the rough past has created mistrust and prejudice on both sides. But the need to collaborate has shown to be beneficial in promoting education cooperation.